Barriers and Facilitators of Physical Activity Participation in Adolescent Girls: A Systematic Review of Systematic Reviews - Duffey, Keeva; Barbosa, Ana; Whiting, Stephen; Mendes, Romeu; Yordi Aguirre, Isabel; Tcymbal, Antonina; Abu-Omar, Karim; Gelius, Peter; Breda, João (Frontiers in Public Health, 2021)
Background: Persistent low physical activity (PA) levels among adolescent girls constitute a public health concern that calls for immediate and evidence-based policy action. This systematic review (SR) aimed to summarize evidence from systematic reviews (SRs) examining the barriers and facilitators of PA participation in adolescent girls. The objectives were to provide a synthesis of the available evidence and identify key areas for fostering gender-responsive action and policy implications. Methods: A comprehensive search of relevant SR and meta-analyses was performed in PubMed and Cochrane Library, until February 2021. Studies were included if they were SRs or meta-analysis, included adolescent girls aged between 10 to 19 years old, and described barriers or facilitators of PA. Two independent authors performed the screening of potentially eligible studies and both assessed the methodological quality of included studies using the AMSTAR 2 tool. The barriers and facilitators were synthesized in environmental, interpersonal, and individual levels. Results: A total of eight SRs were included in the qualitative synthesis. The most frequent barriers identified were the lack of support from peers, family, and teachers, and the lack of time. The most reported facilitators were weight loss, and support from peers, family, and teachers. Key areas for action and policy implementation include an inclusive approach to curriculum development to address gender norms; adequate training of professionals so they have a range of skills to ensure inclusion of adolescent girls; environmental changes in and out of schools to stimulate participation to allow adolescent girls to be active in a safe and attractive environment; multistakeholder support at local, regional, and national level in incorporating a gender-responsive approach towards PA participation. Conclusion: The results highlight the variety of factors that influences adolescent girls’ PA participation. For the attainment of effective policies that increase PA levels in adolescent girls, it is essential to engage several stakeholders at different levels in incorporating a gender-responsive approach towards physical activity participation.